Whakamanahia Te mātauranga o te Māori: empowering Māori knowledge to support Aotearoa’s aquatic biological heritage - Ataria, James; Mark-Shadbolt, Melanie; Mead, Aroha Te Pareake; Prime, Kevin; Doherty, Jim; Waiwai, James; Ashby, Tohe; Lambert, Simon; Garner, Gary Owen (New Zealand Journal of Marine and Freshwater Research, 2018)
As Aotearoa New Zealand grapples with developing solutions to complex issues surrounding its unique freshwater and marine biological heritage, there is a growing recognition that mātauranga Māori can be ‘unlocked’ and used with great effect alongside western science. Examples where appropriate consideration and development of robust methodologies for the application of mātauranga Māori coexisting alongside western science are increasing. Unfortunately, despite the benefits that can be derived from this collaboration, the quality of engagement is not always satisfactory often due to poor interpersonal relationships and misidentification of the knowledge holders. By providing an appropriately historical context, this article is able to consider the critical issues now facing mātauranga and the Māori knowledge holders today, and fundamental requirements that will empower application of this knowledge within bio-heritage management. We consider how the development of a methodology between mātauranga Māori holders and potential end-users might contribute to improved outcomes for Aotearoa’s biological heritage.
Keywords: environmental management; indigenous rights; mātauranga māori; sovereignty; tiriti o waitangi/treaty of waitangi; whakapapa

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori

Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination